2020
DOI: 10.1002/jbmr.4699
|View full text |Cite
|
Sign up to set email alerts
|

Lifelong Excess in GH Elicits Sexually Dimorphic Effects on Skeletal Morphology and Bone Mechanical Properties

Abstract: Excess in growth hormone (GH) levels, seen in patients with acromegaly, is associated with increases in fractures. This happens despite wider bones and independent of bone mineral density. We used the bovine GH (bGH) transgenic mice, which show constitutive excess in GH and insulin‐like growth factor 1 (IGF‐1) in serum and tissues, to study how lifelong increases in GH and IGF‐1 affect skeletal integrity. Additionally, we crossed the acid labile subunit (ALS) null (ALSKO) to the bGH mice to reduce serum IGF‐1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…(15) The effects of active acromegaly on the different compartments and envelopes of bone at the organ level are scarcely studied. Recent experimental studies indicated sexual dimorphism on the skeletal effects of chronic GH and IGF-1 excess (16) complicated by local GH-stimulated IGF-1 and corresponding IGF-binding protein production. (5,17) Based on bone mineral density (BMD) measurements of the hip (TH) and femoral neck (FN) by dual X-ray absorptiometry (DXA), structural information can be derived (hip structure analysis [HSA]) (18,19) and be of importance for understanding the biomechanical competence of the appendicular skeleton and the interplay between the different envelopes in acromegaly.…”
Section: Introductionmentioning
confidence: 99%
“…(15) The effects of active acromegaly on the different compartments and envelopes of bone at the organ level are scarcely studied. Recent experimental studies indicated sexual dimorphism on the skeletal effects of chronic GH and IGF-1 excess (16) complicated by local GH-stimulated IGF-1 and corresponding IGF-binding protein production. (5,17) Based on bone mineral density (BMD) measurements of the hip (TH) and femoral neck (FN) by dual X-ray absorptiometry (DXA), structural information can be derived (hip structure analysis [HSA]) (18,19) and be of importance for understanding the biomechanical competence of the appendicular skeleton and the interplay between the different envelopes in acromegaly.…”
Section: Introductionmentioning
confidence: 99%